"Remember Spain!" Edith Wharton and the Book She Never Wrote. Issue 2 (17th February 2017) - Gómez Reus, Teresa
ABSTRACT: Edith Wharton was an indefatigable traveller who was drawn to Europe's landscapes and cultural heritage. Her footsteps across France and Italy have been carefully traced by her biographers and critics. The fact, however, that the writer's infatuation with Europe also encompassed Spain has been largely overlooked in Wharton criticism. This article draws together published and archival materials, such as her unpublished letters about Spain, the Spain Diary and the typescript A Motor-Flight through Spain, to shed new light on Wharton's complex engagement with this country and on the writing she produced in the wake of her Spanish journeys. Besides uncovering the influence that the Hispanist Royall Tyler had on her interest for this corner of Europe, this essay explores Wharton's A Motor-Flight through Spain, places this unpublished script in dialogue with A Motor-Flight through France and finally offers an explanation for why this projected travelogue never saw the light of day.